Klse Composite Index And Macroeconomic Fundamental Dynamic Interactions - Yu, Teik Beng (2005)

(untitled)
This thesis employs Granger causality test to investigate causal relations and dynamic interactions among Malaysia’s macroeconomic variables and Kuala Lumpur Stock Exchange Composite Index (KLCI).